2003
DOI: 10.1097/01.sla.0000081086.37779.1a
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in the Mediastinal Lymph Node Staging of Nonsmall Cell Lung Cancer

Abstract: PET has the highest accuracy in the mediastinal staging of NSCLC, but is not generally used yet. EUS-FNA has the potential to perform mediastinal tissue sampling more accurate than TBNA, PTNB, and mediastinoscopy, with fewer complications and costs. Although promising, EUS-FNA is still experimental. Mediastinoscopy is still considered as gold standard for mediastinal staging of NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 94 publications
1
66
1
Order By: Relevance
“…EUS-FNA is a safe, less invasive alternative to mediastinoscopy, which is also complimentary, offering access to nodal stations that a single surgical approach would find more difficult to access [11,[17][18][19]. While EUS-FNA has not been directly compared with transbronchial FNA, the latter has recognised limitations, being only 50-70% sensitive and 92-100% specific in assessing malignant mediastinal lymph node involvement in NSCLC and carrying a complication rate of 2-5% [20,21]. The suitability of EUS-FNA for staging of NSCLC is further highlighted by the lack of PET centres in Australia and overseas, requiring many clinicians to perform more invasive mediastinoscopy to histologically prove stage III disease.…”
Section: Discussionmentioning
confidence: 99%
“…EUS-FNA is a safe, less invasive alternative to mediastinoscopy, which is also complimentary, offering access to nodal stations that a single surgical approach would find more difficult to access [11,[17][18][19]. While EUS-FNA has not been directly compared with transbronchial FNA, the latter has recognised limitations, being only 50-70% sensitive and 92-100% specific in assessing malignant mediastinal lymph node involvement in NSCLC and carrying a complication rate of 2-5% [20,21]. The suitability of EUS-FNA for staging of NSCLC is further highlighted by the lack of PET centres in Australia and overseas, requiring many clinicians to perform more invasive mediastinoscopy to histologically prove stage III disease.…”
Section: Discussionmentioning
confidence: 99%
“…25 We thus compared the segmentation performance for both small and large lymph nodes in Table II. Small lymph nodes are defined as having longest diameter less than 1 cm, while large nodes have longest diameter greater than 1 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical data revealed that CT itself is not sufficient to identify mediastinal lymph node involvement in patients with NSCLC (Luke et al, 1986;Lowe et al, 1998;Schimmer et al, 2006). The main problem is the fact that CT only depicts the shape and size of mediastinal lymph nodes, rather than actual tumor involvement (Kramer and Groen, 2003). During recent years PET has become a commonly used technique for the evaluation of mediastinal lymph nodes.…”
Section: Discussionmentioning
confidence: 99%